An experimentally refined tool to assess the risks of the human dermal exposure to herbicide chlorotoluron - Bányiová, Katarína; Čupr, Pavel; Kohoutek, Jiří (Environmental science and pollution research international, 2015)
Dermal absorption of the herbicide chlorotoluron was measured using ex vivo pig skin in Franz diffusion cells in an automated system. The steady-state flux was calculated, as well as the permeability coefficient, which is 0.0038 cm h(-1). The permeability coefficient (Kp) is a key factor when predicting human health risks resulting from dermal exposition to a substance. The experimental determination of this parameter filled data gaps regarding the dermal absorption of chlorotoluron. The experimental permeability coefficient was subsequently used to calculate the dermal absorbed dose during some exposure scenarios. Reference doses were revised, and screening risk assessment process was done to calculate the risks resulting from exposure to chlorotoluron. This refined new approach proved to be a useful tool for human health risk assessment in the areas with these herbicide applications. Graphical Abstract An experimentally refined tool to assess the risks of the human dermal exposure to herbicide chlorotoluron.
Keywords: Skin Absorption; Phenylurea Compounds; kožní absorpce; Risk Assessment; mužské pohlaví; Sus scrofa; fenylmočovinové sloučeniny; herbicidy; hodnocení rizik; zvířata; Humans; Skin; permeabilita; Permeability; Herbicides; kůže; lidé; Male; Animals